NAVIGATING DIGITAL FLOWS: THE IMPACT OF DIGITALTRANSFORMATION ON SUSTAINABLE ECONOMIC GROWTH - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
Digital transformation has become the main driving factor of economic growth in the modern era. This study aims to analyse the effect of digital transformation on sustainable economic growth. The method used in this research is literature. The results show that digital transformation has great potential to increase efficiency, productivity, and innovation, thereby promoting economic growth. However, the research also revealed challenges in navigating the digital flows, such as the digital divide, labour market disruption, and environmental impacts. The findings emphasise the importance of a comprehensive and collaborative approach in managing digital transformation to ensure inclusive and sustainable economic growth. Policy implications and suggestions for further research are also discussed in this study.